[¹¹C] choline as a potential PET/CT biomarker of liver cirrhosis: A prospective pilot study. Issue 6 (June 2021) - Schmilovitz-Weiss, Hemda; Boltin, Doron; Groshar, David; Domachevsky, Liran; Rosenbaum, Eli; Issa, Nidal; Sapoznikov, Boris; Goren, Idan; Issachar, Assaf; Cohen-Naftaly, Michal; Weiss, Avraham; Gingold-Belfer, Rachel; et al.
Abstract: Aim of the study: To compare [¹¹C] choline PET/CT findings between patients with cirrhosis and normal liver controls. Methods: Included 11 patients with cirrhosis and 14 controls. All underwent a dynamic [11C] choline PET/CT. The maximal standard uptake values (SUVmax), the area under the curve (AUC) and kinetic parameters (K1 and K2), clinical and laboratory data, were compared between groups. Results: Patients mean age was 68.4 ± 10.7 and controls, 69.7 ± 7.3 years. Mean SUVmax was higher in patients than controls (right lobe, 10.06 ± 12 vs. 6.3 ± 1.6, P  = 0.011; left lobe, 8.6 ± 11.6 vs. 5.4 ± 0.9, P  = 0.024; spleen 17.99 ± 27.8 vs. 13.4 ± 2.6, P  = 0.027; kidney, 35.9 ± 59.5 vs. 19.3 ± 4.8, P  = 0.025) and also AUC values (right lobe, 13, 538 ± 20, 020 vs. 8427.3 ± 1557.9, P  = 0.026; left lobe 12, 304 ± 18, 871 vs. 6878.9 ± 1294.3, P  = 0.024; spleen, 12, 875 ± 17, 930 vs. 8263.9 ± 1279.2, P  = 0.023; kidney, 24, 623 ± 36, 025 vs. 13, 667 ± 3873.9, P  = 0.032). No difference in kinetic parameters was found. No correlations between severity of clinical signs and imaging-derived parametric data were found among patients with cirrhosis. Conclusions: [11C] choline PET/CT may serve as a noninvasive biomarker for patients with cirrhosis.